1978
DOI: 10.1177/002193477800800308
|View full text |Cite
|
Sign up to set email alerts
|

Interracial Marriages

Abstract: Interracial marriages have garnered attention periodically since the turn of the century. However, sociopsychological research in the area of intermarriage continues to be scant in spite of increased contact between the races in the 1960s. Social scientists have maintained the study of intermarriage may provide a precise, quantitative measurement of crucial and related questions such as the process of assimilation, the degree of internal cohesion in individual racial, religious, and ethnic groups, and the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Classic and new assimilation theories perceive marriages between majority and (migrant) minority groups as a means to or/and a result of immigrants' integration into their host societies (Alba/Nee 1997;Aldridge 1978;Gordon 1964). Elwert (2018) highlighted that "intermarriage lies between the poles of social openness and social restraints" (Elwert 2018: 14); it is connected with social structure (Blau 1977;Blau/Becker/Fitzpatrick 1984), and social status (Davis 1941).…”
Section: Introductionmentioning
confidence: 99%
“…Classic and new assimilation theories perceive marriages between majority and (migrant) minority groups as a means to or/and a result of immigrants' integration into their host societies (Alba/Nee 1997;Aldridge 1978;Gordon 1964). Elwert (2018) highlighted that "intermarriage lies between the poles of social openness and social restraints" (Elwert 2018: 14); it is connected with social structure (Blau 1977;Blau/Becker/Fitzpatrick 1984), and social status (Davis 1941).…”
Section: Introductionmentioning
confidence: 99%
“…Blacks had more favorable attitudes toward interracial marriages than Whites (Aldridge, 1978;Sones, 1988;Spickard, 1989). Tucker and Mitchell-Kernan (1990) also found that White partners of Black/White marriages tend to encounter ostracism from friends and relatives within their community more frequently than their Black spouses.…”
Section: Theoretical Discussion and Hypothesis Derivationmentioning
confidence: 99%
“…Delores Aldridge (1978) deeply examined the empirical and theoretical considerations concerning interracial marriages especially in the American context. With reference to these considerations, Delores Aldridge (1978) specifies by citing Barron (1946: 249), that 'Social scientists have maintained the study of intermarriage may provide a precise, quantitative measurement of crucial and related questions such as the process of assimilation, the degree of internal cohesion in individual racial, religious, and ethnic groups, and the extent of social distance between groups of these types'. To a certain degree, these empirical and theoretical considerations seem to be applicable in the South African context of interracial marriages.…”
Section: A Brief Overview Of Diversity and Marriagementioning
confidence: 99%
“…Delores Aldridge (1978: 367-8), citing Staples (1973, indicates that 'the intermingling of young adults of different races at the high school and college levels is widely expected to be reflected over the long run in an increased rate of intermarriages…. And the fact that large numbers of interracial couples meet on college campuses away from home reduces the amount of parental and community control over the choice of an individual's dating partners.…”
Section: A Brief Overview Of Diversity and Marriagementioning
confidence: 99%